Cytokine Kinetics in Febrile Neutropenic Children: Insights on the Usefulness as Sepsis Biomarkers, Influence of Filgrastim, and Behavior of the IL-23/IL-17 Pathway. (9th July 2017) - Araujo, Orlei Ribeiro de; Salomão, Reinaldo; Brunialti, Milena Karina Coló; Silva, Dafne Cardoso Bourguignon da; Senerchia, Andreza Almeida; Moraes Costa Carlesse, Fabianne Altruda de; Petrilli, Antonio Sergio
Abstract : Background. The study aimed to describe the kinetics of various cytokines from day 1 to day 14 of the onset of fever in neutropenic children and to evaluate their performances as discriminators of sepsis in the first 24 hours of fever, the possible influence of filgrastim, and the functioning of the IL-23/IL-17 axis. Methods. IL-1 β, TNF- α, IL-10, IL-12/23p40, IL-21, IL-6, IL-8, IL-17, G-CSF, and GM-CSF were measured in plasma on days 1, 2, 3, 5, and 14 from the onset of fever in 35 patients. Results. Thirteen patients (37.1%) developed sepsis. In mixed models, IL-6, IL-8, IL-10, and G-CSF showed higher estimated means in septic patients (P < 0.005 ), and IL-12/23p40 and IL-17 in nonseptic patients (P < 0.05 ). On day 1, IL-6, IL-8, and IL-10 appeared upregulated in patients who received filgrastim. Only IL-6, IL-8, IL-10, and procalcitonin were useful as discriminators of sepsis. Associating the markers with each other or to a risk assessment model improved performance. Conclusions. Cytokines kinetics showed proinflammatory and anti-inflammatory responses similar to what is described in nonneutropenic patients. IL-8, IL-6, IL-10, and procalcitonin are useful as early biomarkers of sepsis. Filgrastim upregulates expression of these markers, and we observed deficiency in the IL-23-IL-17 axis accompanying sepsis.